2023
DOI: 10.1212/nxi.0000000000200103
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on DR and DQ Human Leukocyte Antigens in Anti-LGI1 Encephalitis

Abstract: Background and ObjectivesTo explore the clinical characteristics and HLA associations of patients with anti–leucine-rich glioma-inactivated 1 encephalitis (LGI1E) from a large single center in Israel. Anti-LGI1E is the most commonly diagnosed antibody-associated encephalitic syndrome in adults. Recent studies of various populations reveal significant associations with specific HLA genes. We examined the clinical characteristics and HLA associations of a cohort of Israeli patients.MethodsSeventeen consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…This study also confirmed the particular demographic characteristics of the non- DRB1∗07 : 01 carriers and, in addition, established a secondary association, both in DRB1∗07 : 01 heterozygous and noncarriers, with another allele, DRB1∗04 : 02 [63 ▪▪ ]. This allele is especially frequent in Jewish populations and, accordingly, was recently reported in another study from Israel [64 ▪ ]. Likewise, young female Chinese patients that are non- DRB1∗07 : 01 seem to carry more frequently DRB1∗03 : 01 [65].…”
Section: Anti-leucine-rich Glioma-inactivated 1 Encephalitissupporting
confidence: 84%
“…This study also confirmed the particular demographic characteristics of the non- DRB1∗07 : 01 carriers and, in addition, established a secondary association, both in DRB1∗07 : 01 heterozygous and noncarriers, with another allele, DRB1∗04 : 02 [63 ▪▪ ]. This allele is especially frequent in Jewish populations and, accordingly, was recently reported in another study from Israel [64 ▪ ]. Likewise, young female Chinese patients that are non- DRB1∗07 : 01 seem to carry more frequently DRB1∗03 : 01 [65].…”
Section: Anti-leucine-rich Glioma-inactivated 1 Encephalitissupporting
confidence: 84%
“…LGI1 (e.g., HLA-DRB1Ã07:01, HLA-DQA1Ã02:01) [80][81][82][83]84 && ], and Caspr2 (e.g., HLA-DRB1Ã11:01) [85,86] encephalitis. By contrast, HLA-related predisposition is weaker in NMDAR encephalitis [83,87].…”
Section: Triggers Of Antibody-mediated Encephalitis and Development O...mentioning
confidence: 99%